Quadriceps Tendon Graft Anatomy in the Skeletally Immature Patient. Issue 7 (10th July 2019) - Shea, Kevin G.; Burlile, Jessica F.; Richmond, Connor G.; Ellis, Henry B.; Wilson, Philip L.; Fabricant, Peter D.; Mayer, Stephanie; Stavinoha, Tyler; Troyer, Stockton; Dingel, Aleksei B.; Ganley, Theodore J.
Background: The quadriceps tendon (QT) is increasingly considered for primary and revision anterior cruciate ligament reconstruction in skeletally immature patients, as it may be harvested as a purely soft tissue graft with considerable tissue volume. Because of distinct rectus tendon (RT) separation from the QT complex, the potential for RT retraction exists and could lead to QT weakness after QT graft harvest. Purpose: To describe the anatomy of the pediatric QT and clarify decussation of the RT and QT to avoid the risk of delayed RT retraction and QT weakness after QT graft harvest. Study Design: Descriptive epidemiology study. Methods: Nine cadaveric knee specimens (aged 4-11 years) underwent gross dissection. Coronal-plane width and depth of the QT were measured at intervals proximal to the superior pole of the patella at distances of 0.0, 0.5, 1.0, and 1.5 times the length of the patella. The distance was measured from the superior patellar pole to the point of RT separation from the remainder of the deeper/posterior QT. Results: The median patellar length was 28 mm (interquartile range, 26-37 mm). The coronal-plane width of the QT was larger superficially/anteriorly when closest to the patella but wider when measured deeper/posteriorly as the tendon extended proximally. The median distance between the superior pole of the patella and RT separation from the QT was 0.95 times the patellar length. The distance to widening of the deeper/posterior aspect of the QT was 1.14 times the patellar length proximal to the patella. Conclusion: The RT begins a distinct separation from the QT above the superior pole of the patella at a median of 0.95 times the patellar length in skeletally immature specimens. The deeper/posterior aspect of the QT begins to increase in coronal-plane width proximally after a distance of 1.14 times the patellar length above the knee, while the superficial/anterior aspect of the tendon continues to narrow. Awareness of the separation of the RT from the QT, and the coronal-plane width variation aspects of the QT proximally, is important for surgeons utilizing the QT as a graft to avoid inadvertent release of the RT from the rest of the QT complex.